Старожитня західноукраїнська ойконімія (етимологія зниклих назв поселень колишньої Львівської землі Руського воєводства к. XIV – поч. XV ст.) - Редьква, Я. П. (Беларуская навука, 2022)
The article provides an etymological analysis and restored the place of historical locality of the seven historical Western Ukrainian oikonyms - *Hermaniv, *Dobro[v]trychi, *Zushytsi, *Osovytsia, *Staroduby, *Strilyscha, *Schyretska Volia - settlements of the former Lviv Land of Ruske Voivodeship from the end of the 14th - beginning of the 15th centuries (between 1375 and 1416). Oikonyms make up a fragment of integral picture of the original settlement of these lands and indicates to ethnic processes that happened here in the Middle Ages.
Keywords: oikonym, etymology, regional oikonymy, historical settlement processes, toponymic system